Investigation of current models of care for genetic heart disease in Australia: A national clinical audit. (1st May 2021) - Austin, Rachel; Quinn, Michael C.J.; Afoakwah, Clifford; Metke-Jimenez, Alejandro; Leroux, Hugo; Atherton, John; Brown, Jaye S.; Wornham, Linda J.; Macciocca, Ivan; de Silva, Michelle G.; Thompson, Tina; Martin, Ellenore M.; et al.
Abstract: Background: This sub-study of the Australian Genomics Cardiovascular Genetic Disorders Flagship sought to conduct the first nation-wide audit in Australia to establish the current practices across cardiac genetics clinics. Method: An audit of records of patients with a suspected genetic heart disease (cardiomyopathy, primary arrhythmia, autosomal dominant congenital heart disease) who had a cardiac genetics consultation between 1st January 2016 and 31 July 2018 and were offered a diagnostic genetic test. Results: This audit included 536 records at multidisciplinary cardiac genetics clinics from 11 public tertiary hospitals across five Australian states. Most genetic consultations occurred in a clinic setting (90%), followed by inpatient (6%) and Telehealth (4%). Queensland had the highest proportion of Telehealth consultations (9% of state total). Sixty-six percent of patients had a clinical diagnosis of a cardiomyopathy, 28% a primary arrhythmia, and 0.7% congenital heart disease. The reason for diagnosis was most commonly as a result of investigations of symptoms (73%). Most patients were referred by a cardiologist (85%), followed by a general practitioner (9%) and most genetic tests were funded by the state Genetic Health Service (73%). Nationally, 29% of genetic tests identified a pathogenic or likely pathogenic gene variant; 32% of cardiomyopathies, 26% of primary arrhythmia syndromes, and 25% of congenital heart disease. Conclusion: We provide important information describing the current models of care for genetic heart diseases throughout Australia. These baseline data will inform the implementation and impact of whole genome sequencing in the Australian healthcare landscape. Highlights: We describe the current models of care for genetic heart diseases throughout Australia Genetic testing identified a causative variant in 29% of cases Data will inform the implementation and impact of whole genome sequencing in Australian healthcare